2006
DOI: 10.1007/s11270-006-3055-6
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Magnitude of Atmospheric Fluxes of Total Inorganic Nitrogen and Other Inorganic Species to the Tampa Bay Watershed, FL, USA

Abstract: We estimated the total inorganic fluxes of nitrogen (N), sulfur (S), chloride (Cl − ), sodium (Na + ), calcium (Ca 2+ ), magnesium (Mg 2+ ), potassium (K + ) and hydronium (H + ). The resistance deposition algorithm that is programmed as part of the CALMET/CALPUFF modeling system was used to generate spatially-distributed deposition velocities, which were then combined with measurements of urban and rural concentrations of gas and particle species to obtain dry deposition rates. Wet deposition rates for each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
2
6
0
2
Order By: Relevance
“…The calculation of V d is based on a simple parameterization of experimental meteorological measurements to determine atmospheric transport characteristics (Slinn, 1982;Zhang et al, 2001). The magnitudes of V d estimated were 1.2 and 0.6 cm/s for NO − 3 and NH + 4 , respectively and 2 cm/s for PO 3− 4 , 1.2 cm/s for TN and ON and 2 cm/s for TP and OP, which are consistent with results reported in the literature (Duce et al, 1991;Prospero et al, 1996;Spokes et al, 2000;Herut et al, 2002, Poor et al, 2006. These estimated V d could result in an uncertainty of a factor of 2-3 in the calculated fluxes (Duce et al, 1991).…”
Section: Dry Depositionsupporting
confidence: 91%
“…The calculation of V d is based on a simple parameterization of experimental meteorological measurements to determine atmospheric transport characteristics (Slinn, 1982;Zhang et al, 2001). The magnitudes of V d estimated were 1.2 and 0.6 cm/s for NO − 3 and NH + 4 , respectively and 2 cm/s for PO 3− 4 , 1.2 cm/s for TN and ON and 2 cm/s for TP and OP, which are consistent with results reported in the literature (Duce et al, 1991;Prospero et al, 1996;Spokes et al, 2000;Herut et al, 2002, Poor et al, 2006. These estimated V d could result in an uncertainty of a factor of 2-3 in the calculated fluxes (Duce et al, 1991).…”
Section: Dry Depositionsupporting
confidence: 91%
“…Although the deposition of K + from energy production and industrial plants has decreased in some European countries [ 255 ], that of K + from agricultural activities is very high in some developing countries, such as Brazil, reaching 55% of total K + deposition [ 256 ]. K + deposition linked to industrial and mainly agricultural activities can be higher than deposition from natural processes [ 257 , 258 ], such as sea spray [ 259 , 260 ]. The inputs of K + from atmospheric deposition have a determinant role in K + balances of forests, counteracting the loss of K + from leaching, which is favored by N deposition, due indirectly to soil pH decrease and soil degradation and directly to the competition with ammonium for the occupation of the exchangeable complex [ 261 , 262 ].…”
Section: Role Of K In Terrestrial Ecosystemsmentioning
confidence: 99%
“…deposition of K from energy production and industrial plants has decreased in some European countries (Ruoho-Airola & Salminen, 2003). Some studies have observed that K deposition, linked to industrial and, frequently, agricultural activities, can represent a higher proportion than that from natural processes (Ferm & Hultberg, 1999;Golobocanin et al 2009) such as sea spray (Poor et al, 2006;Prathibha et al, 2010).…”
Section: Anthropogenic Impacts On the K Cycle K Fertilizersmentioning
confidence: 99%